Role of Human Resource Practices in Knowledge Spillover: Study of Knowledge Hubs - Mehreen Waheed (JISR Management and Social Sciences & Economics, 2023)
The aim of this study is to identify the significant role of HR practices in the knowledge spillover process that drives firm innovation and to ascertain doable HR- practices to accelerate this process. For data collection, semi-structured interviews were conducted. Interviews were transcribed. For analysis, phenomenology is used as a research methodology to cater the essence of the phenomenon (knowledge spillover process) by studying HR-managers lived experiences. Findings validated through subjective saturated evidence of informants. The results based on data analysis revealed that frequent employee interactions, cooperative work environment and participative leadership are considered as the essence of knowledge spillovers. Another objective is fulfilled as Training and development and Employee relations are the two major HR practices that facilitate the knowledge spillover process effectively. This research benefits both academicians and practitioners. For educationist, it propounded a conceptual framework that supports in theory enhancement. For practitioners, effective implementation of HR practices can open new avenues of success for organizations.